Effects of a soccer training session fatigue on balance ability - Gioftsidou, A. F.; Malliou, P.; Pafis, G.; Beneka, A.; Godolias, G. (Journal of Human Sport & Exercise, 2011)
The purpose of the present study was to investigate the effects of a soccer training session on the balance ability of the young soccer players. Participants were twenty-six young soccer players. Standard testing balance boards and Biodex Stability System were used to assess balance ability before (pre-training) and immediately after (post-training) the completion of a soccer training session. Also, Isokinetic knee joint moment measurements (60°/sec and 180°/sec) were carried out pre- and post-soccer training. The results revealed that no differences (p>0.05) were found in balance ability and knee joint moment production between pre- and post-soccer training. Result is in contrast to the notion of a link between fatigue induced by a soccer training session or game and injury caused by impaired balance.